Numerical Simulation for Solar Hybrid Photovoltaic Thermal Air Collector. (2016) - pauly, Lippin; Rekha, L.; Vazhappilly, Christy V.; Melvinraj, C.R.
Abstract: Solar energy is one of the renewable energy sources which have potential for future energy applications. The current well-liked technology converts solar energy into electricity and heat individually. In this paper, an effort is made to simulate and evaluate the overall performance of a hybrid photovoltaic thermal (PV/T) air collector using computational fluid dynamics (CFD) software. The numerical analysis of the flow and heat transfer in hybrid PV/T systems is computationally quite complicated and the number of research works on this topic is quite low. Based on numerical analysis, the performance of a solar hybrid PV/T air collector has been studied. The numerical simulation was done in commercial software ANSYS FLUENT 14.5.0. The electrical energy conversion in solar cell was calculated with user defined function. The numerical results are validated with experimental results from literature. The results show a good agreement between experimental and simulated result for outlet air temperature and PV cell temperature. Using validated model, effect of mass flow rate and duct depth on the performance of solar hybrid PV/T collector has been studied and optimum values are identified. In order to increase the overall performance of a solar hybrid PV/T air collector, a novel design is proposed here. The result shows in the proposed design gives 20% enhancement in overall performance compared to conventional solar hybrid PV/T air collector.